Limits and DEs

Calculus Level 5

If d y d x = x ( 1 + y 2 ) 2 ln y ( 1 y 2 ) \displaystyle \frac {dy}{dx} = - \frac {x(1+y^{2})^{2}}{\ln y (1-y^{2})} , y ( 1 ) = 1 y(1)=1 and lim y x ( y ) = A π B + C \displaystyle \lim_{y \to \infty} x(y) = \sqrt{\frac {A \pi}{B} + C} , where A A and B B are coprime positive integers, find the value of A + B + C A + B + C .


The answer is 4.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Use separation of variables to integrate for x x : d y d x = x ( 1 + y 2 ) 2 ln ( y ) ( 1 y 2 ) \frac {dy}{dx} = - \frac {x\,(1+y^{2})^{2}}{\ln(y) \,(1 - y^{2})} x d x = ln ( y ) 1 y 2 ( 1 + y 2 ) 2 d y \therefore \int x\,\mathrm{d}x = - \int \ln(y)\,\frac {1-y^{2}}{(1+y^{2})^{2}} \,\mathrm{d}y 1 2 x 2 = ln ( y ) 1 y 2 ( 1 + y 2 ) 2 d y \frac {1}{2}x^{2} = - \int \ln(y)\,\frac {1-y^{2}}{(1+y^{2})^{2}} \,\mathrm{d}y Now use integration by parts to evaluate the right-hand-side where f ( y ) = 1 y 2 ( 1 + y 2 ) 2 f'(y) = \frac {1-y^{2}}{(1+y^{2})^{2}} , g ( y ) = ln ( y ) g(y) = \ln(y) and hence g ( y ) = 1 y g'(y) = \frac {1}{y} . To find f ( y ) f(y) use partial fractions where z = y 2 z=y^{2} : 1 z ( 1 + z ) 2 = A ( 1 + z ) 2 + B 1 + z \frac {1-z}{(1+z)^{2}} = \frac {A}{(1+z)^{2}} + \frac {B}{1+z} 1 z = A + B ( 1 + z ) 1-z = {A} + B\,(1+z) When z = 1 z = -1 , A = 2 A = 2 , hence B = 1 B = -1 for all z z . Rewriting the expression for f ( y ) f(y) , now use the substitution u = arctan y u = \arctan y and d y = sec 2 u d u \mathrm{d}y = \sec^{2}u\,\mathrm{d}u for the integral on the left side. f ( y ) = 2 ( 1 + y 2 ) 2 d y 1 1 + y 2 d y f(y) = \int \frac {2}{(1+y^{2})^{2}}\,\mathrm{d}y - \int \frac {1}{1+y^{2}}\,\mathrm{d}y f ( y ) = 2 ( 1 + tan 2 u ) 2 sec 2 ( u ) d u arctan y f(y) = \int \frac {2}{(1+\tan^{2}u)^{2}\,\sec^{2}(u)}\,\mathrm{d}u - \arctan y f ( y ) = 2 cos 2 ( u ) d u arctan y f(y) = \int 2\cos^{2}(u)\,\mathrm{d}u - \arctan y Use the identity cos 2 u = 2 cos 2 ( u ) 1 \cos 2u = 2\cos^{2}(u) - 1 to simplify: f ( y ) = cos 2 u + 1 d u arctan y f(y) = \int \cos 2u +1 \,\mathrm{d}u - \arctan y = 1 2 sin 2 u + u arctan y = \frac {1}{2} \sin 2u + u - \arctan y = sin u cos u + u arctan y = \sin u \cos u + u - \arctan y = sin ( arctan y ) cos ( arctan y ) + arctan y arctan y = \sin (\arctan y) \cos (\arctan y) + \arctan y - \arctan y Use the identities sin ( arctan y ) = y 1 + y 2 \sin (\arctan y) = \frac {y}{\sqrt{1+y^{2}}} and cos ( arctan y ) = 1 1 + y 2 \cos (\arctan y) = \frac {1}{\sqrt{1+y^{2}}} to obtain f ( y ) = y 1 + y 2 f(y) = \frac {y}{1+y^{2}} . Now we can go back to the original integral using integration by parts. 1 2 x 2 = ln ( y ) 1 y 2 ( 1 + y 2 ) 2 d y \frac {1}{2}x^{2} = - \int \ln(y)\,\frac {1-y^{2}}{(1+y^{2})^{2}} \,\mathrm{d}y 1 2 x 2 = y 1 + y 2 ln y + 1 y . y 1 + y 2 d y \frac {1}{2}x^{2} = - \frac {y}{1+y^{2}}\,\ln y + \int \frac {1}{y}.\frac {y}{1+y^{2}} \,\mathrm{d}y 1 2 x 2 = y 1 + y 2 ln y + arctan y + c \frac {1}{2}x^{2} = - \frac {y}{1+y^{2}}\,\ln y + \arctan y + c Substitute the point (1, 1) to obtain the constant of integration: 1 2 = π 4 + c \frac {1}{2} = \frac {\pi}{4} + c c = 1 2 π 4 c = \frac {1}{2} - \frac {\pi}{4} 1 2 x 2 = y 1 + y 2 ln y + arctan y + 1 2 π 4 \frac {1}{2}x^{2} = -\frac {y}{1+y^{2}}\,\ln y + \arctan y + \frac {1}{2} - \frac {\pi}{4} x = ± 2 y 1 + y 2 ln y + 2 arctan y + 1 π 2 x = \pm \sqrt{-\frac {2y}{1+y^{2}}\,\ln y + 2\arctan y + 1 - \frac {\pi}{2}} To satisfy the condition y ( 1 ) = 1 y(1)=1 , the negative result is ignored. x = 2 y 1 + y 2 ln y + 2 arctan y + 1 π 2 x = \sqrt{-\frac {2y}{1+y^{2}}\,\ln y + 2\arctan y + 1 - \frac {\pi}{2}} lim y x ( y ) = lim y 2 y 1 + y 2 ln y + 2 arctan y + 1 π 2 \lim_{y \to \infty} x(y) = \lim_{y \to \infty} \sqrt{-\frac {2y}{1+y^{2}}\,\ln y + 2\arctan y + 1 - \frac {\pi}{2}} As y y \to \infty , 2 y 1 + y 2 ln y 0 -\frac {2y}{1+y^{2}}\,\ln y \to 0 and 2 arctan y π 2\arctan y \to \pi . Hence the limit becomes: 0 + π + 1 π 2 = π 2 + 1 \sqrt{0 + \pi + 1 - \frac {\pi}{2}} = \sqrt{\frac {\pi}{2} + 1} A + B + C = 4 \therefore A + B + C = \boxed{4}

A Really nice problem and equally good solution!

Prakhar Bindal - 4 years, 3 months ago

it can be integrated more easily by doing +1-1 and write (1+y^2)^2 as (1-y^2)^2+4y^2

A Former Brilliant Member - 4 years, 3 months ago

If we take y= tan θ \tan \theta and integrate by parts .....it can be solved easily.

Samarth Agarwal - 4 years, 3 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...